ПРО ПОСЛІДОВНИЙ МЕТОД КЛАСИФІКАЦІЇ - Осипчук, Михайло Михайлович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
A task is examined about the evaluation of probabilities of that an object belongs each of two aggregates. We consider known his independent descriptions. The method of classification of such objects is built.